Debt-Equity Composition of International Investment. (IMF Working Papers; Working Paper ;, 1988)
Capital flows to the nonindustrial countries share three striking characteristics. First, the bulk, of these flows was in the form of debt, not equity; second, the loans were mostly to, or guaranteed by, debtor governments; and third, these debts were largely bank loans, not bonds. This paper examines the economic factors that may have been responsible.